2019
DOI: 10.1371/journal.pone.0225099
|View full text |Cite
|
Sign up to set email alerts
|

Dissociations of oral foci of infections with infectious complications and survival after haematopoietic stem cell transplantation

Abstract: IntroductionHaematopoietic stem cell transplantation (HSCT) recipients are at increased risk for severe infections. This study examined the associations of common oral infections with survival and infectious complications in HSCT recipients.Materials and methodsAll autologous and allogeneic HSCT recipients transplanted in the University Hospital of Basel, Switzerland, between 2008 and 2016 and referred to oral infection control pre-HSCT were included in this retrospective case-control study. All patients had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
1
8
0
5
Order By: Relevance
“…A systematic review by Koka and Gupta also reported that a reduced tooth count was associated with higher mortality [ 35 ]. However, a recent retrospective case-control study recommended that radical dental interventions to chronic oral infections could be postponed until post-hematopoietic stem cell transplantation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Koka and Gupta also reported that a reduced tooth count was associated with higher mortality [ 35 ]. However, a recent retrospective case-control study recommended that radical dental interventions to chronic oral infections could be postponed until post-hematopoietic stem cell transplantation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A relação entre alterações sistêmicas e a condição de saúde bucal tem sido relatada nos últimos anos. Neste contexto, já foram descritas associação entre doença periodontal e endocardite, doenças cardiovasculares, acidente vascular cerebral, artrite reumatoide, doenças do sistema respiratório, doença renal, parto prematuro e diabetes (Weidlich et al, 2008;Mauramo et al, 2019;Schuurhuis et al, 2016).…”
Section: -Fase Precoce Do Tcth E a Cavidade Bucalunclassified
“…Mesmo a cavidade bucal sendo um potencial foco de infecção para o paciente criticamente imunossuprimido, há poucos estudos que relacionam a condição de saúde bucal com as complicações do TCTH. O único estudo que avaliou esta relação, foi a avaliação retrospectiva de 341 pacientes europeus submetidos ao TCTH alogênico realizada por Mauramo et al, (2019). Apesar de encontrarem má condição de saúde bucal, 7% apresentavam pelo menos um potencial foco infeccioso em cavidade bucal no pré-TCTH, 64% apresentavam doença periodontal e média de CPOD de 18,7.…”
Section: -Fase Precoce Do Tcth E a Cavidade Bucalunclassified
See 2 more Smart Citations